Electrical Resistivity, Tribological Behaviour of Multiwalled Carbon Nanotubes and Nanoboron Carbide Particles Reinforced Copper Hybrid Composites for Pantograph Application - N. Selvakumar; K. Gangatharan (Advances in Materials Science and Engineering)
This work focuses on the influence and contribution of multiwalled carbon-nanotube (MWCNT)–boron carbide (B4C) to the mechanical and tribological properties of copper matrix composites. Different weight fractions of nano- B4C-containing fixed-weight fractions of MWCNT-reinforced copper composites were prepared using the entrenched cold-press sintering method of powder metallurgy. The wear losses of sintered Cu–MWCNT–B4C composites were investigated by conducting sliding tests in a pin-on-disc apparatus. The addition of reinforcements showed enhancements in the hardness and wear properties of the composites due to the uniform dispersion of the secondary reinforcement in the copper matrix and the self-lubricating effect of the MWCNTs. The effects of the nanoparticle distribution in the matrix, the worn surface morphology, and the elemental composition of the composites were characterized using high-resolution scanning electron microscopy and X-ray diffraction analysis. The electrical resistivity of the fabricated copper hybrid composite preforms was evaluated using a four-point probe tester. Our results highlight the use of experiential reinforcing limits of B4C on the wear and electrical and mechanical behaviour of copper composites.